Antifertility effect of betel nut (Areca catechu L) in male rat - Rahman, Ave Olivia; Purwakanthi, Anati; Dewi, Hasna (MEDISAINS, 2020)
Background: Betel nut (Areca catechu L) are traditional beverages in Jambi. Betel nut high dose has a cytotoxic effect on testis and other organs—limited data about the effect of betel nut as male antifertility.Purposes:  This study aimed to determine the effect of infertility on betel nut use at a dose of 50 mg/kg body weight (BW) in male rats.   Methods: Ten male Sprague Dawney rats that had passed the fertility test, aged 2-3 months and weighing 150-200 grams ware used in this study. The rat was grouped into two groups randomly. Group 1, as the negative control, were received aqua dest, and group 2 was treated by betel nut with dose 50 mg/kg BW for 35 days. When terminated, testis weight weighed using micro scales. Blood collected for measuring testosterone levels. Histopathology assessment of testis used Hematoxylin Eosin Staining and sperm counting from cauda epididymis.Results: The weight of testis in the group received betel nut was lower than the control group. The histopathology of testis showed shrunk, reduced the diameter of seminiferous tubules, and like cytolytic lesions in the germinal layer—the total sperm number and progressive sperms also lower than the control group (p<0.05). There was no abnormality in Leydig cell and interstitium tissue.  Male rats after treatment could not impregnate the female rats.Conclusion: Betel nut at dose 50 mg/kg BW have antifertility activity in male rats.